2023
DOI: 10.2147/jaa.s423884
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Healthy Diet on Asthma and Wheezing in Children and Adolescents: A Systematic Review and Meta-Analysis

Jin Zhang,
Mengyang He,
Qiduo Yu
et al.

Abstract: Background Asthma is a public health problem requiring focused attention. This study aimed to systematically evaluate the association between dietary structure and asthma or wheezing in children. Methods The study protocol of this meta-analysis has been registered in the International Prospective Register of Systematic Reviews (PROSPERO) with the registration code CRD42023390191. A total of 8397 articles were retrieved, searching PubMed, Medline, Embase, Web of Science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 107 publications
(251 reference statements)
0
5
0
Order By: Relevance
“…Starting from asthma and allergies, the findings suggested an inverse association. As confirmed by a recently published systematic review [39] that aimed to underline the effects of a healthy diet on asthma and wheezing in children and adolescents, the effect of the MD on asthma was more prominent. The Mediterranean Diet has been linked to a lower risk of asthma in numerous epidemiological studies [40].…”
Section: Asthma and Allergiesmentioning
confidence: 78%
“…Starting from asthma and allergies, the findings suggested an inverse association. As confirmed by a recently published systematic review [39] that aimed to underline the effects of a healthy diet on asthma and wheezing in children and adolescents, the effect of the MD on asthma was more prominent. The Mediterranean Diet has been linked to a lower risk of asthma in numerous epidemiological studies [40].…”
Section: Asthma and Allergiesmentioning
confidence: 78%
“…In a meta-analysis conducted by Garcia-Marcos et al, it was found that the Mediterranean diet was significantly associated with a reduced prevalence of asthma (OR: 0.86; 95% CI 0.78–0.95; p = 0.004) ( Garcia-Marcos et al, 2013 ). Similarly, a meta-analysis by Zhang et al, reported protective effects of a Mediterranean diet on asthma (OR = 0.88; 95% CI: 0.79–0.97; p = 0.014) ( Zhang et al, 2023 ). However, further research is required to gain a deeper understanding of the specific role of the microbiome in individuals with asthma who adhere to a Mediterranean diet.…”
Section: Infancy and Childhood Imprint Developmentmentioning
confidence: 97%
“…In addition, based on the diet hypothesis, nutrients and food components may have a significant impact on the immune system and pathways related to allergic inflammation [12]. This influence can occur directly or indirectly through the modulation Pharmaceuticals 2024, 17, 670 2 of 31 of gut microbiota [14,15]. Consequently, these factors can either contribute to or protect against allergic diseases [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This influence can occur directly or indirectly through the modulation Pharmaceuticals 2024, 17, 670 2 of 31 of gut microbiota [14,15]. Consequently, these factors can either contribute to or protect against allergic diseases [14][15][16][17]. Given that diet is a highly changeable and easily available intervention, it is crucial to identify specific nutrients, food components, or dietary patterns that might be used as preventive or therapeutic measures for allergic diseases.…”
Section: Introductionmentioning
confidence: 99%